As práticas de responsabilidade social corporativa e seus impactos no comprometimento do funcionário com a empresa: uma análise em empresas cearenses de serviços - Silva, Suely Mendonça de Oliveira e (2005)
The growing number of investments in social projects by modern enterprises shows that they are trying to achieve competitive sustainable advantage focusing on a humanistic approach. Considering that social responsibility seems to be important nowadays not only for the companies - because of the ethical and human position adopted – but also for people who appreciate this kind of attitude, the main goal of this study is to check if – and how – adopting responsible social procedures contributes to making employees more committed to the company. The survey was applied to the Personnel (career employees) from three large companies in Ceará, winners of the Delmiro Gouveia Award in social performance (awarded by the Local Stock Market). It was verified that social procedures may influence employee’s behaviour and attitude and may contribute to their affectionate commitment to the company. However, it was perceived that it is less likely that these projects will have a significant effect over the employees if the company does not have social positive attitudes towards them, such as offering good promotion prospects, holding employees in high regard, contributing to their satisfaction at work, considering their dedication and performance among others.